Keberadaan Anisakis typica (Anisakidae) dari Ikan Tongkol dan Ikan Layang dari perairan Sulawesi Barat - Muhammad Dusil Hafid; Hilal Anshary (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Anisakis (L3-stage) is a parasitic nematode commonly found in marine fish or squid serve as intermediate or paratenic host. The purpose of this research was to identify Anisakis larvae using PCR-RFLP and sequencing methods. A total of 30 individuals of each species: bullet tuna (Auxis rochei) and Indian scad(Decapterus russeli) were examined for presence of Anisakis spp. Fish samples caught by fishermen around Mamuju waters were purchased at a fish market. The fish was necropsied and the organs: liver, intestine wall, heart and muscle were removed and put on separated petri dishes and examined for parasites under a stereo microscope. Anisakis found was cleaned and fixed in 70% alcohol. Initial identification was based on ventriculus shape and presence of mucron to distinguish Anisakis type I and Anisakis type II. All Anisakis found belong to Anisakis type I. Ten Anisakis type I were isolated, cleaned and stored in microfuge tubes containing 70% alcohol. The parasite gDNA was extracted using Wizard genomic DNA extraction and purification kit (Promega).Species of Anisakis was determined by PCR-RFLP at ITS1-5.8S-ITS2 region using two restriction enzymes: Taq I and Hinf I and PCR-sequencing in mtDNA cox2 region. Analysis by PCR-RFLP showed that all Anisakis type Iexamined was in the same pattern as Anisakis typica. Sequencing in mtDNAcox-2 region and the phylogenetic analysis showed that all samples were in the same cluster as A. typica. Based on PCR-RFLP and sequencinganalysis, all Anisakis found in this study belong to A. typica.